Investigation of solar radiation effects on the energy performance of the (Al2O3–CuO–Cu)/H2O ternary nanofluidic system through a convectively heated cylinder - Adnan; Abbas Waseem; Ghodhbani Refka; Ghachem Kaouther; Walelign Tadesse; Khan Yasir; Akermi Mehdi; Hassani Rym (Open Physics)
Thermal transport in ternary nanofluid is a topic of interest in different engineering systems. These fluids have higher thermal conductivity than traditional nanofluids. Hence, the present study aims to develop a new ternary nanofluid model for a cylindrical working domain. For this, thermophysical properties of ternary nanoliquids and appropriate transformations are used. The problem is then investigated through a numerical approach and the comparative results are obtained. The ternary nanofluid shows an optimum decrease in the velocity due to the involvement of three types of nanoparticles. Suction of the fluid with strength α=0.1,0.9,1.7,2.5α =0.1,\hspace{.5em}0.9,\hspace{.5em}1.7,\hspace{.5em}2.5 and Reynolds effects Re=1.0,1.5,2.0,2.5\text{Re}=1.0,\hspace{.5em}1.5,\hspace{.5em}2.0,\hspace{.5em}2.5 significantly control the motion and dominant behaviour is examined for a simple nanofluid. The thermal capability of the nanofluids is enhanced against the concentration factor ϕ1=0.01,0.0.3,0.05,0.07{φ }_{1}=0.01,0.0.3,0.05,0.07 while suction phenomena resist the temperature. Inclusion of radiations (Rd=0.1,0.5,0.9,1.3)(\text{Rd}\hspace{.25em}=\hspace{.25em}0.1,0.5,0.9,1.3) and convective transport (Bi=0.01,0.02,0.03,0.04B_{i}=0.01,0.02,0.03,0.04) contribute dominantly for thermal applications in nanofluids. The shear drag magnitude changes from 107.4995 to 162.287% (TNF), 113.427 to 170.666% (HNF), and 120.886 to 180.704% (SNF) for varying ϕ1{φ }_{1} from 1.0 to 7.0%. Further, the efficiency of TNF, HNF, and SNF showed a prominent increase from 42.0126 to 68.8055% (TNF), 40.6019 to 66.6076% (HNF), and 39.8879 to 65.5324% (SNF), for stronger Biot effects from 0.5 to 2.0. Hence, the study’s outcomes would help to address the heat transfer issues from multiple aspects.